Analisa pemilihan supplier dengan metode Analytic Hierarchy Process: Kasus Perusahaan Otomotif di Sunter - Estu Adi Sambudi (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
The selection of a competent supplier is the one important factor to be able to compete with other companies. PT. XYZ, a company located in Sunter, is engaged in automotive manufacturing. In the period of 2017 PT. XYZ has several lines stop due to several factors, such as the delivery of raw materials which is often late, resulting in the availability of raw materials on the production line is less, incompatibility the goods compared to the specifications. Eight of them are stamping suppliers. The purpose of this study is to design an AHP (Analytic Hierarchy Process) model that can be used to determine the criteria and the score of that, also determine the alternative suppliers which are the main priority in selecting supplier stamping.  Based on the data processing using the AHP method, obtained 5 criteria, Quality, price, delivery, capability, and service. The highest criteria’s value is quality with score 30%. While the priority of stamping supplier is PT C (12,49) and PT E is the supplier which is not prioritized because it is in the lowest position (5,68).